Risk of Recurrent Venous Thromboembolism in Autoimmune Diseases: A Systematic Review of the Literature - Borjas-Howard, Jaime Francisco; Leeuw, Karina de; Rutgers, Abraham; Meijer, Karina; Tichelaar, Vladimir Ynse Ieuwe Gerardus (Seminars in Thrombosis and Hemostasis, 2019)
Despite an abundance of literature on the risk of a first venous thromboembolic event (VTE) in autoimmune diseases, specific recommendations about managing VTE in autoimmune diseases are lacking. This article aimed to collect evidence on the risk of recurrent VTE in patients with autoimmune diseases. The authors searched PubMed/Embase for studies including patients with VTE and autoimmune diseases as an exposure or studies including patients with autoimmune diseases in which recurrent VTE was one of the outcomes. Eleven articles were selected from 4,739 unique abstracts. Of the 11 studies, 3 reported time-dependent rates. Two studies collected rates of recurrence in Behcet's disease, reporting a 5-year recurrence risk between 35 and 40%. However, the 5-year recurrence risk was lower than 10% in patients treated with immunosuppressant medication, while two studies suggested frequent recurrence in patients on only anticoagulant therapy. The other study reporting time-dependent incidence concerned patients with inflammatory bowel disease and index VTE. The 5-year risk of recurrent VTE was 33.4%, yielding a hazard ratio of 1.7 versus controls. All studies were retrospective and therefore risk may overestimate recurrence risk in comparison with known prospective cohort studies. There are insufficient data to make confident recommendations about the management of recurrent VTE prevention in patients with autoimmune diseases in general. The overall VTE risk profile, lower effectiveness of anticoagulants, and the observation that immunosuppression lowered risk of recurrence in patients with Behcet's disease seem to warrant immunosuppressant therapy over anticoagulation as a first consideration when preventing VTE recurrence in these patients.
Keywords: venous thromboembolism; autoimmune disease; rheumatoid arthritis; risk